Blind detection of orthogonal space-time block coding based on ICA schemes - GU Bo1; LIU Ju1; XU Hong-ji1 (Tongxin xuebao)
By introducing information in both space and time domain, transmit diversity gain could be achieved by or-thogonal space-time block coding （OSTBC）, and higher coding gain could be obtained without sacrifice of bandwidth. However the decoding required accurate channel state information （CSI）, which strongly determined the system per-formance. The independent component analysis （ICA） based blind source separation （BSS） techniques could be used to detect the transmitted signals without channel estimation. Two new schemes were proposed based on ICA blind detection by exploiting the orthogonality of OSTBC. And meanwhile some detecting algorithms based on channel estimation were used for performance evaluation. Simulation results for Rayleigh fading channels demonstrated that the two new schemes could enhance the flexibility of the communication system while achieve better bit error rate （BER） performance.